Effect of Fatty Acid Derivatives on Rumen Methane and Propionate In Vitro - Van Nevel, C. J. (1971)
The effect of several fatty acid derivatives on methane and propionate in the rumen is described. A possible explanation for the observed inverse relationship between methane and propionate is given.